Tumor rupture of gastric gastrointestinal stromal tumors during endoscopic resection: a risk factor for peritoneal metastasis? - Song, Shiyi; Ren, Wei; Wang, Yi; Zhang, Shu; Zhang, Song; Liu, Fei; Cai, Qiang; Xu, Guifang; Zou, Xiaoping; Wang, Lei (Endoscopy International Open, 2018)
Background and study aims Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors in the gastrointestinal tract. Up to the present time, complete surgical excision has been the standard treatment for primary GISTs greater than 2 cm. It is well known that tumor rupture during surgery is an independent risk factor for peritoneal metastasis; however, it is not known whether the risk of peritoneal metastasis increases in cases where the tumor is ruptured during endoscopic resection.Patients and methods A total of 195 patients treated for GIST between January 2014 and December 2016 in our hospital were enrolled in this study. They were divided into two groups according to whether the tumor was ruptured during endoscopic resection. The rate of peritoneal metastasis in patients in the two groups who also suffered perforation was investigated from the follow-up results.Results Approximately 55.4 % of all patients were female and the average age of the study group was 59.0 ± 10.3 years. Of the 195 patients, the tumors in 27 were ruptured and the remaining 168 patients underwent en bloc resection. There was no statistically significant difference in gender or age between the two groups. The median tumor size (maximum diameter) in all patients was 1.5 cm (0.3 – 5.0 cm): 2.5 cm (0.8 – 5.0 cm) and 1.4 cm (0.3 – 4.0 cm) in the tumor rupture group and en bloc resection group, respectively (P < 0.001). Most of the tumors were located in the gastric fundus. At a median follow-up of 18.7 ± 10.2 months, neither tumor recurrence (liver metastasis, peritoneal metastasis, local recurrence) nor mortality related to GISTs were detected.Conclusions Tumor rupture during endoscopic resection of gastric GISTs may not be a risk factor for peritoneal metastasis.